Temporal distribution of leprosy prevalence in northeastern capitals between 2014 and 2021 (Research, Society and Development, 2022)
Brazil is the second country in the world with the highest number of leprosy cases, with the Northeast being the third region most affected by leprosy. This study aims to carry out the temporal distribution of the prevalence of leprosy in the Northeastern capitals, during the period from 2014 to 2021, associated with the operational data of each location. This is an epidemiological, retrospective, descriptive study with a quantitative approach, in which secondary data from the Notifiable Diseases Information System (SINAN) were used. Microsoft Excel 2019 software was used for data tabulation and preparation of graphs and tables. The highest prevalence was found in the city of São Luís-MA, with a predominance of males and individuals over 60 years old. Regarding operational indicators, Natal-RN stood out for registering the highest proportion of new cases (96.50%) and also for detection by referral (85.99%). As for the degree of physical disability, operational class, and exit mode, all states recorded a higher proportion for grade 0, multibacillary, and cure. The study concluded that there is a greater active search in places with higher prevalence, but there is a need for training for health professionals.